Tourist Attractions And Destination Image To Loyalty Of Travellers Through Satisfaction (Case Study of Tanah Karo Agrotourism Destination) - Dedy Suranta Sinukaban; Elfitra Desy Surya; Nurafrina Siregar (Yayasan Multidimensi Kreatif, 2023)
This study aims to analyze the influence of the analysis of tourist attractions and destination image on tourist loyalty through satisfaction (A case study of Tanah Karo agrotourism destination). Based on the identification of problems, several critical issues were found, such as less attractive tourist attractions, negative destination images, and declining tourist satisfaction and loyalty. This study is limited to tourists aged 18-55 years and domiciled outside Tanah Karo Kota. The sample was taken using the purposive sampling method with a total of 115 respondents. The data was analyzed using Structural Equation Modeling (SEM) using the Smart Partial Least Squares (PLS) method. The results of the study show that all variables, tourist attractions, and destination image have a positive and significant influence on tourist loyalty mediated by satisfaction. The hypothesis with the highest score is the effect of satisfaction on loyalty with an original sample value (O) of 0.670 and a T-statistic of 6.005. On the other hand, the hypothesis with the lowest value is the influence of tourist attractions on tourist loyalty mediated by satisfaction with an original sample value (O) of 0.205 and a T-Statistic of 2.426. The conclusion of this study emphasizes the importance of improving tourist attractions, and destination image, to increase tourist loyalty mediated by satisfaction. Suggestions for Tanah Karo agro-tourism industry players to focus on innovating tourist attractions, and improving the image of destinations for tourists to visit to increase tourist loyalty mediated by satisfaction.